2017
DOI: 10.5301/jbm.5000241
|View full text |Cite
|
Sign up to set email alerts
|

XRCC1Arg399Gln Gene Polymorphism and Hepatocellular Carcinoma Risk in the Italian Population

Abstract: To our knowledge, this is the first study reporting an association between BER SNP and HCC risk in a population of central-southern Italy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…BER mechanism involves the tightly coordinated function of four kind of enzymes that correct single base modifications that do not distort DNA helix (glycosylase, apurinic/apyrimidinic endonuclease –APE1–, polymerase, and ligase) [ 73 ]. The association of the rs25487 polymorphism of X-ray repair cross-complementing protein 1 (XRCC1), one of the main factors of BER mechanism, with the risk of HCC is well known [ 82 ]. Moreover, patients with the wild-type genotype (GG) receiving TACE containing a platinum derivative had a worse prognosis than patients carrying AA or GA genotypes [ 64 ].…”
Section: Dna Repairing (Moc-4)mentioning
confidence: 99%
“…BER mechanism involves the tightly coordinated function of four kind of enzymes that correct single base modifications that do not distort DNA helix (glycosylase, apurinic/apyrimidinic endonuclease –APE1–, polymerase, and ligase) [ 73 ]. The association of the rs25487 polymorphism of X-ray repair cross-complementing protein 1 (XRCC1), one of the main factors of BER mechanism, with the risk of HCC is well known [ 82 ]. Moreover, patients with the wild-type genotype (GG) receiving TACE containing a platinum derivative had a worse prognosis than patients carrying AA or GA genotypes [ 64 ].…”
Section: Dna Repairing (Moc-4)mentioning
confidence: 99%
“…Likewise, in another study done among 100 HCC patients recruited from the Capital of Egypt, the authors identified that XRCC1 (rs25487*399Gln) allele revealed a statistically significant with an elevated risk of HCC ( p = 0.004) 13 . Furthermore, other reports confirmed the contribution of the XRCC1 (rs25487*p.Gln399Arg) variant with the elevated risk of HCC like those among Italian, 48 Chinese, 49 and Pakistani 50 subjects. However, we encountered two studies that confirmed no significant association of the XRCC1 (rs25487*p.Gln399Arg) variant with the susceptibility of HCC like those among Polish, 25 and French 51 subjects.…”
Section: Discussionmentioning
confidence: 94%
“…After the full-text assessment, 17 articles were excluded for reviews and editorials and 8 articles were excluded for lack of detailed genotype distribution data, finally, 32 articles were included in qualitative and quantitative synthesis. 4,8,[10][11][12][13] In the 32 included articles, 24 studies including 4106 HCC patients and 4295 controls were about the XRCC1 rs25487 polymorphism, 9 studies concerning 1355 HCC patients and 1376 controls were about the XRCC1 rs25489 polymorphism and 11 studies with 2067 HCC patients and 2183 controls were about the XRCC1 rs1799782 polymorphism. The summarized basic information of the 32 included studies, involving first author, publication year, region, race, genotyping method, sample size, the genotype distribution in case and control groups, quality score and P value for HWE, are presented in Table 1.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%